Proposal for temperature-independent optical sensor based on asymmetric Mach–Zehnder interferometer - Luo, Yanxia; Yin, Rui; Ji, Wei; Huang, Qingjie; Cui, Jianmin; Jiang, Shouzhen; Gong, Zisu; Liu, Fengyu (Optical and quantum electronics, 2021)
An optical sensor based on dual asymmetric Mach–Zehnder interferometers (AMZIs) cascade with temperature-independent is proposed. The optical sensor based on AMZI is very sensitive to the change of ambient temperature. The temperature shift will lead to the change of the refractive index of the optical waveguide, which will affect the accuracy of the measurement of target-parameters. The designed optical sensor is composed of two AMZIs cascaded, one acting as a sensing AMZI and the other as a compensating AMZI. When the temperature changes, the sensing curve of the sensing AMZI shifts. The compensating AMZI can make the sensing curve goes into reverse to realize the compensation. The error of compensation results is reduced by 2–3 orders of magnitude, the compensation temperature range is from 5 to 45 °C, and the error is reduced to < 0.1%. This cascade compensation structure can be used not only for based on AMZI optical sensor, but for other interference optical devices.